2019
DOI: 10.2967/jnumed.119.229567
|View full text |Cite
|
Sign up to set email alerts
|

Promise of Fully Integrated PET/MRI: Noninvasive Clinical Quantification of Cerebral Glucose Metabolism

Abstract: We describe a fully automated processing pipeline to support the noninvasive absolute quantification of the cerebral metabolic rate for glucose (CMRGlc) in a clinical setting. This pipeline takes advantage of "anatometabolic" information associated with fully integrated PET/MRI. Methods: Ten healthy volunteers (5 men and /5 women; 27 ± 7 y old; 70 ± 10 kg) underwent a test-retest 18 F-FDG PET/MRI examination of the brain. The imaging protocol consisted of a 60-min PET list-mode acquisition with parallel MRI ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Therefore a Logan graphical analysis is assumed to be less dependent on the accurate determination of the rapidly changing peak of the input function which could be poorly estimated 23 . This is confirmed by several previous studies 25 , 38 , 39 . However, since metabolization of [ 18 F]JNJ-739 is rather fast (only 30% ± 5% of parent tracer at 20 min post-injection), the contribution of later time points of the metabolite-corrected arterial plasma input function is limited such that cumulated activity concentrations at later time points, which are used for the Logan graphical analysis estimation, are more dependent on the accurate estimation of peak activity concentrations, shortly after tracer injection.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore a Logan graphical analysis is assumed to be less dependent on the accurate determination of the rapidly changing peak of the input function which could be poorly estimated 23 . This is confirmed by several previous studies 25 , 38 , 39 . However, since metabolization of [ 18 F]JNJ-739 is rather fast (only 30% ± 5% of parent tracer at 20 min post-injection), the contribution of later time points of the metabolite-corrected arterial plasma input function is limited such that cumulated activity concentrations at later time points, which are used for the Logan graphical analysis estimation, are more dependent on the accurate estimation of peak activity concentrations, shortly after tracer injection.…”
Section: Discussionsupporting
confidence: 92%
“…Using TOF MR angiography can improve the delineation of the arterial volume in PET [184,[189][190][191]. The IDIF could be implemented in an automated pipeline to provide absolute values of cerebral glucose metabolism in a clinically feasible manner [192]. The IDIF measured from either MRI and PET could also be used interchangeably [193].…”
Section: Emerging Clinical and Research Applicationsmentioning
confidence: 99%
“…60 , 61 Studies have reported intrasubject variability of up to 25% in test–retest comparisons even in healthy people scanned at close points in time under well-controlled research conditions. 62 As a result, [ 18 F]FDG PET requires careful control of scanning conditions (for example, patient fasting) and its sensitivity is limited to detect only relatively large changes or group differences, approximately 25% or greater. 62 In contrast, our present results and previous test–retest data with [ 11 C]UCB-J PET suggest that changes in synaptic density as small as 10% can be identified, which could allow for the detection of earlier or subtler disease effects.…”
Section: Discussionmentioning
confidence: 99%
“…62 As a result, [ 18 F]FDG PET requires careful control of scanning conditions (for example, patient fasting) and its sensitivity is limited to detect only relatively large changes or group differences, approximately 25% or greater. 62 In contrast, our present results and previous test–retest data with [ 11 C]UCB-J PET suggest that changes in synaptic density as small as 10% can be identified, which could allow for the detection of earlier or subtler disease effects. The data presented here support the assertion that in vivo [ 11 C]UCB-J binding can be interpreted as a static measure of SV2A protein density with negligible influence of variability in brain function.…”
Section: Discussionmentioning
confidence: 99%